Bitten wir im Bittgebet? - Gasteiger, Marisa Hanna (Zeitschrift für katholische Theologie, 2019)
The article »Bitten wir im Bittgebet?« (»Do we ask for something in petitionary prayers?«) first briefly outlines the philosophical problems that occur in petitionary prayer and then examines the necessary and sufficient conditions of the speech act »request« and applies these to God as addressee. It also deals with theological attempts to interpret the speech act »request« which overlook the conditions I have described. I will evaluate these interpretations and show that it is not possible to uncouple petitionary prayer from the speech act »request«.